Method for improving strength of Portland cement with high iron phase content

By adding nanocomposite chemical admixtures to silicate cement with high-iron phase content, the reaction activity is stimulated and the pore structure is optimized, and the problem of slow increase in the strength of silicate cement in high-iron phase content is solved, achieving the simultaneous strength of early and later stages Improve and improve wearability and production costs.

CN119241177APending Publication Date: 2025-01-03NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411469679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The strength of silicate cement with high-iron phase content increases slowly, and the early hydration exothermic heat is high, and it is easy to generate internal stress and lead to cracks. The increase in C4AF content leads to weak development of strength in the early 3D, poor wearability, and limited development of strength in the 28D.

Method used

When the high-iron phase content of silicate cement clinker is mixed with water, nanocomposite chemical additives are added to the cement slurry. The nanocomposite material consists of hydrated calcium silicate nanomaterial and polycarboxylate ether (PCE). Combining chemical admixtures such as triethanolamine (TEA), triisopropanolamine (TIPA), diethanol monoisopropanolamine (DEIPA), stimulate the reactivity of the iron aluminate phase and optimize the pore structure.

Benefits of technology

It significantly improves the early and later strength of high-iron phase content silicate cement, improves the abrasion of cement clinker, reduces production costs, and in the strength of cement mortar in 1 day, 3 days, 7 days and 28 days respectively The increase was 26.5%~41%, 13.6%~19.2%, 5%~11.4%, 0%~16.0%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241177A_ABST
    Figure CN119241177A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing the strength of Portland cement with high iron phase content, which is characterized in that a nano composite chemical admixture is doped into the Portland cement with high iron phase content to improve the hydration reaction activity of the cement and optimize the pore structure, thereby enhancing the strength of the Portland cement with high iron phase content. By adopting the enhancing method disclosed by the invention, the early strength and the later strength of the cement can be improved. According to GB / T17671-1999, the mortar strength of the Portland cement doped with the nano-composite chemical admixture for 1 day, 3 days, 7 days and 28 days is improved by 26.5%-41%, 13.6%-19.2%, 5%-11.4% and 0%-16.0% respectively compared with the mortar strength of the Portland cement not doped with the nano-composite chemical admixture for the high iron phase content, and the application effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of civil engineering materials, and in particular relates to a method for improving the strength of silicate cement with high iron content. Background Art

[0002] Traditional Portland cement clinker is mainly composed of tricalcium silicate (C3S), dicalcium silicate (C2S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF), of which the content of C3S is about 50%~70%. Cement with higher C3S content usually exhibits poor durability because it shrinks in volume during hydration and hardening, resulting in cracks. The early hydration heat release is high, which is prone to internal stress and cracking. The content of calcium oxide (CaO) in high C3S is very high, and the corresponding carbon emissions are high. With the reduction of high-quality limestone and the application of low-grade raw materials, this will lead to a decrease in the CaO content and C3S content in the clinker. Therefore, the content of the other three minerals will inevitably increase. Many manufacturers will consider the adaptability of cement and the chemical composition of raw materials. Generally, the mineral composition is designed by stabilizing the C3A content and increasing the C4AF content. However, the increase in C4AF content will lead to weak early strength development at 3d (low C3S content; after the implementation of GB173-2023, cement companies have higher requirements for 3d strength), poor grindability (high solvent phase content, and C4AF and C2S are more difficult to grind), and limited strength development at 28d (physical encapsulation and steric hindrance of C4AF phase in clinker particles to silicate phase hinders C3S / C2S hydration). Therefore, developing a method for improving the performance of high iron phase silicate cement has important guiding significance for the sustainable development of cement companies. Summary of the invention

[0003] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for effectively improving the strength performance of silicate cement with high iron content in order to solve the problem that the strength of silicate cement with high iron content is slowly improved.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for improving the strength of high iron content silicate cement, characterized in that, while the high iron content silicate cement clinker is mixed with water, a nano-composite chemical admixture is added to the cement slurry; the content of tetracalcium aluminoferrate in the high iron content silicate cement clinker is not less than 15%; The nanocomposite chemical admixture is formed by mixing a chemical admixture and a nanocomposite material. The chemical admixture is selected from any one of triethanolamine (TEA), triisopropanolamine (TIPA), diethanol monoisopropanolamine (DEIPA) or monoethanolamine diisopropanolamine (EDIPA) or a mixture of two or more thereof. The nanocomposite material contains hydrated calcium silicate nanomaterial and polycarboxylate ether (PCE).

[0005] By adding chemical admixtures, stimulating the reactivity of the ferroaluminate phase and optimizing the pore structure through nanomaterials, the strength properties of silicate cement with high iron content can be improved, while the grindability of cement clinker can be improved and its production cost can be reduced.

[0006] According to existing reports, triethanolamine (TEA), triisopropanolamine (TIPA), diethanol monoisopropanolamine (DEIPA) and monoethanolamine diisopropanolamine (EDIPA) are often used as grinding aids for cement clinker and have a certain strengthening effect on cement. Hydrated calcium silicate nanomaterials (such as CSH gel) are often used to significantly enhance the early strength of cement, but have no effect on the later strength and may even cause strength shrinkage. The present invention finds that the use of the above-mentioned nanocomposite chemical admixtures can not only enhance the early strength of cement, but also have a growth effect on the later strength, thereby improving the strength of silicate cement with a high iron content as a whole.

[0007] Preferably, the high iron content silicate cement clinker of the present invention comprises, by weight percentage, 53% to 54% tricalcium silicate, 25% to 26% dicalcium silicate, 2% to 3% tricalcium aluminate, and 15% to 16% tetracalcium aluminoferrite.

[0008] Preferably, the calcium silicate hydrate nanomaterial described in the present invention includes any one of CSH gel, CFSH gel, and CASH gel, or a mixture of two or more thereof.

[0009] Preferably, the particle specific surface area of ​​the high iron content silicate cement clinker of the present invention is 340-360m 2 / kg.

[0010] Preferably, the dosage of the chemical admixture described in the present invention is 0.02% to 0.05% of the mass of cement.

[0011] Preferably, the nanocomposite material of the present invention is added in an amount of 0.5% to 0.1% of the mass of cement.

[0012] Alternatively, the chemical admixture has a solid content of 85% to 90%, is diluted into a chemical admixture solution with a solid content of 1% to 5%, and then is added to the cement slurry or mixed in the cement mixing water during the cement mixing process.

[0013] Alternatively, the nanocomposite material is dispersed in water to form a nanocomposite material solution with a solid content of 10% to 15%, and then added to cement slurry or mixed in cement mixing water during cement mixing.

[0014] Alternatively, the chemical admixture has a solid content of 85% to 90%, and is dispersed in water together with the nano-composite material to form a nano-composite chemical admixture solution; in the nano-composite chemical admixture solution, the solid content of the chemical admixture is 1% to 5%, and the solid content of the nano-composite material is 10% to 15%; the nano-composite chemical admixture solution is then added to the cement slurry during the cement mixing process or mixed in the cement mixing water.

[0015] Preferably, the mass ratio of the nanocomposite chemical admixture solution to cement mixing water is 1:(2-6). Beneficial Effects

[0016] The present invention improves the strength of the silicate cement with high iron content by adding a nano-composite chemical admixture to the silicate cement with high iron content to improve the hydration reaction activity of the silicate cement with high iron content and optimize the pore structure. Compared with the silicate cement with high iron content not added with the nano-composite chemical admixture, the cement mortar strength of the silicate cement with high iron content added with the nano-composite chemical admixture after 1 day, 3 days, 7 days and 28 days is increased by 26.5% to 41%, 13.6% to 19.2%, 5% to 11.4% and 0% to 16.0% respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0018] Figure 1 This is the effect of grinding the clinker with different dosages of nano-composite chemical admixtures after grinding for 30 minutes. (K:0 A1:0.5%-0.02% A2:1%-0.02% A3:0.5%-0.05% A4:1%-0.05%) Figure 2 The XRD spectrum of the high iron content silicate cement clinker used in the present invention. DETAILED DESCRIPTION

[0019] The present invention can be better understood with reference to the following examples.

[0020] In the following examples, the composition of the mixed materials used is shown in Table 1.

[0021] Table 1 Cement, CSH / PCE, DEIPA mass percentage (wt. / %)

[0022] Test method: The clinker strength test is carried out in accordance with the national standard GB / T17671~1999.

[0023] The specific surface area is determined according to the national standard GB / T8074~2008.

[0024] The mineral content in the clinker was obtained by fitting the full XRD spectrum, and the calculation was implemented using the HighScorePlus software package based on the Rietveld method.

[0025] First, the high iron content silicate cement clinker is ground. Figure 1 The graphs are D50 and D90 of clinker after 30 minutes of grinding at different dosages of nanocomposite chemical admixtures. The present invention uses nanocomposite chemical admixtures compounded with CSH / PCE and DEIPA to explore the degree of improvement in the grindability of clinker at dosages of 0.5%-0.02%, 1%-0.02%, 0.5%-0.05%, and 1%-0.05%. It can be found that the effect of CSH / PCE-DEIPA at each dosage on the improvement of the grindability of silicate cement clinker with a high iron content is better than that of the control example, indicating that CSH / PCE-DEIPA is helpful for the grinding of silicate cement clinker with a high iron content.

[0026] In the following examples, the high iron content silicate cement clinker used was ground to a specific surface area of ​​340-360 m 2 / kg powder; chemical composition is shown in Table 2; mineral composition is shown in Table 3; XRD spectrum is shown in Figure 2 shown. Example 1

[0027] The high iron content silicate cement with a content of 0.5% CSH / PCE and 4% gypsum was molded according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Example 2

[0028] The silicate cement with high iron content and a DEIPA content of 0.02% and a gypsum content of 4% was molded according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Example 3

[0029] CSH / PCE with a dosage of 0.5% and DEIPA with a dosage of 0.02% were stirred at a stirring rate of 100 r / min for 10 min to obtain a CSH / PCE-DEIPA nanocomposite chemical admixture with a dosage of 0.5%-0.02%; then, it was molded with silicate cement with a high iron content of 4% gypsum at a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Example 4

[0030] CSH / PCE with a content of 1% and DEIPA with a content of 0.02% were stirred at a stirring rate of 100 r / min for 10 min to obtain a CSH / PCE-DEIPA nanocomposite chemical admixture with a content of 1%-0.02%; then, it was molded with silicate cement with a high iron content of 4% gypsum according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Example 5

[0031] CSH / PCE with a dosage of 0.5% and DEIPA with a dosage of 0.05% were stirred at a stirring rate of 100 r / min for 10 min to obtain a CSH / PCE-DEIPA nanocomposite chemical admixture with a dosage of 0.5%-0.05%; then, it was molded with silicate cement with a high iron content of 4% gypsum according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Example 6

[0032] CSH / PCE with a content of 1% and DEIPA with a content of 0.05% were stirred at a stirring rate of 100 r / min for 10 min to obtain a CSH / PCE-DEIPA nanocomposite chemical admixture with a content of 1%-0.05%; then, it was molded with high iron content silicate cement with a gypsum content of 4% according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1. Comparative Example

[0033] Deionized water and 4% gypsum were used to form high iron content silicate cement according to a water-cement ratio of 0.5 and a sand-cement ratio of 3. The mass percentage of the mixture is shown in Table 1.

[0034] Table 2 Chemical composition of clinker (wt / %)

[0035] Table 3 Clinker mineral content (wt / %)

[0036] Table 4 Cement mortar strength

[0037] Table 2 shows the chemical composition of silicate cement clinker with high iron content; Table 3 shows the mineral content of clinker obtained by quantitative XRD full spectrum fitting; Table 4 shows the strength comparison of comparative example and embodiment at different ages.

[0038] As can be seen from Table 4, compared with the comparative example, Example 1 (i.e., 0.5% CSH / PCE was added alone), the strength of Example 1 increased in the early stage and decreased in the later stage; compared with the comparative example, Example 2 (i.e., 0.02% DEIPA was added alone), the strength of Example 2 decreased in the early stage and increased in the later stage. It can be seen that the addition of chemical admixtures or nanocomposites alone cannot achieve the simultaneous increase of the early and late strengths. When the addition amount of the prepared nanocomposite chemical admixture is 0.5%-0.02% (i.e., Example 3) after adding the chemical admixtures or nanocomposites at the same time, Example 3 has better performance than Examples 1 and 2 in both the early and late stages. Therefore, the nanocomposite chemical admixture prepared by the present invention combines the advantages of the two admixtures; it makes up for its own shortcomings and produces a synergistic effect of performance improvement. In addition, compared with the comparative example, the mechanical strength growth rate of Example 3 at 1d is 33.7%, the mechanical strength growth rate at 3d is 18.3%, the mechanical strength growth rate at 7d is 11.4%, and the mechanical strength growth rate at 28d is 16%, showing a good application effect.

[0039] The present invention provides a method and method for improving the strength of high iron content silicate cement. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for improving the strength of high iron content silicate cement, characterized in that: While mixing the high iron content silicate cement clinker with water, adding a nano-composite chemical admixture into the cement slurry; the content of tetracalcium aluminoferrate in the high iron content silicate cement clinker is not less than 15%; The nanocomposite chemical admixture is formed by mixing a chemical admixture and a nanocomposite material. The chemical admixture is selected from any one of triethanolamine, triisopropanolamine, diethanol monoisopropanolamine or monoethanolamine diisopropanolamine or a mixture of two or more thereof. The nanocomposite material contains calcium silicate hydrate nanomaterial and polycarboxylate ether.

2. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The high iron content silicate cement clinker includes, by weight percentage, 53% to 54% tricalcium silicate, 25% to 26% dicalcium silicate, 2% to 3% tricalcium aluminate, and 15% to 16% tetracalcium aluminoferrite.

3. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The calcium silicate hydrate nano material includes any one of CSH gel, CFSH gel and CASH gel or a mixture of two or more thereof.

4. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The specific surface area of ​​the particles of the high iron content silicate cement clinker is 340-360m 2 / kg.

5. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The dosage of the chemical admixture is 0.02% to 0.05% of the cement mass.

6. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The nanocomposite material is added in an amount of 0.5% to 0.1% of the cement mass.

7. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The chemical admixture has a solid content of 85% to 90%, is diluted into a chemical admixture solution with a solid content of 1% to 5%, and then is added to the cement slurry or mixed in the cement mixing water during the cement mixing process.

8. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The nanocomposite material is dispersed in water to form a nanocomposite material solution with a solid content of 10% to 15%, and then added to cement slurry or mixed in cement mixing water during cement mixing.

9. The method for improving the strength of high iron content silicate cement according to claim 1, characterized in that: The solid content of the chemical admixture is 85% to 90%, and the chemical admixture is dispersed in water together with the nano-composite material to form a nano-composite chemical admixture solution; in the nano-composite chemical admixture solution, the solid content of the chemical admixture is 1% to 5%, and the solid content of the nano-composite material is 10% to 15%; then the nano-composite chemical admixture solution is added to the cement slurry during the cement mixing process or mixed in the cement mixing water.

10. The method for improving the strength of high iron content silicate cement according to claim 9, characterized in that: The mass ratio of the nano-composite chemical admixture solution to cement mixing water is 1:(2-6).

Citation Information

Patent Citations

  • Nanocrystal nucleus type early strength cement grinding aid and preparation method thereof

    CN115368052A